2017
DOI: 10.1017/s1463423617000810
|View full text |Cite
|
Sign up to set email alerts
|

Practicing safety: a quality improvement intervention to test tools to enhance pediatric psychosocial care for children 0–3 years

Abstract: BackgroundChild maltreatment is a significant public health issue in the United States. Yet, fewer than half of pediatricians discuss behavioral, developmental, or parenting issues with parents.ObjectiveThis paper describes the testing of bundles of tools and processes, part of a larger intervention, Practicing Safety, targeted at changing physician and staff behavior to identify families at risk for child maltreatment, provide anticipatory guidance, refer to community resources, and follow-up and track at-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Child maltreatment prevention programs (e.g., Safe Environment for Every Kid [SEEK] and Practicing Safety) designed for primary care may also increase caregiver medical adherence after maltreatment (Abatemarco et al, 2018; Dubowitz et al, 2009). These programs screen for and address maltreatment risk factors as well as provide anticipatory guidance about normative child development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Child maltreatment prevention programs (e.g., Safe Environment for Every Kid [SEEK] and Practicing Safety) designed for primary care may also increase caregiver medical adherence after maltreatment (Abatemarco et al, 2018; Dubowitz et al, 2009). These programs screen for and address maltreatment risk factors as well as provide anticipatory guidance about normative child development.…”
Section: Discussionmentioning
confidence: 99%
“…These programs screen for and address maltreatment risk factors as well as provide anticipatory guidance about normative child development. These programs appear to reduce maltreatment, CPS reports, medical non-adherence, and increase provider knowledge of community resources (Abatemarco et al, 2018; Dubowitz et al, 2009). Additionally, although motivational interviewing (MI) is not a specific intervention package, a recent narrative review showed that provider’s use of MI strategies with maltreating parents may increase positive parenting and parental service engagement (Shah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Providing education on addiction to all clincial and support staff as well as training on how to improve interaction and communication with families affected by maternal OUD may be warranted. Previous research within the context of paediatric primary care has shown that accessible resources placed within a framework of quality improvement may enable physicians and staff to modify their practice‐based systems to improve communication with and support and care for patients (Abatemarco et al, 2018). This type of resource, tailored towards the needs of mothers with OUD and their children, may also be beneficial for clinics providing care to this population.…”
Section: Discussionmentioning
confidence: 99%
“…Such stigma may lead to feelings of guilt and shame, which could deter mothers to share honestly about the health of their child or to engage in health promotion programmes and interventions. A previous study of mothers in treatment for OUD found that stigma directly impacted the extent to which mothers engaged in early intervention child development services (Peacock-Chambers et al, 2020 (Abatemarco et al, 2018). This type of resource, tailored towards the needs of mothers with OUD and their children, may also be beneficial for clinics providing care to this population.…”
Section: Support For Opioid Use Disorder Treatment and Recoverymentioning
confidence: 99%
See 1 more Smart Citation